The determinant factors affecting auditors’ ability to detect fraud: Empirical study at public accounting firms in Jakarta and Tangerang - Gracia Gracia; Ratnawati Kurnia (Economics, Management and Sustainability)
The auditor has responsibility to give audit opinion and identify whether the financial statements are free from material misstatement caused by fraud. The purpose of this research is to analyze the effect of competence, independence, time budget pressure, work experience and professional skepticism towards auditor’s ability to detect fraud. The object were auditors working at Public Accounting Firms in Tangerang and Jakarta. Primary data was collected by distributing questionnaires and analyzed by using multiple linear regression. The result are competence, work experience and professional skepticism have positive significant effect towards auditor’s ability to detect fraud. To increase auditor’s ability in detecting fraud, auditors should improve their competence to be able to perform audit in accordance with Professional Standards for Certified Public Accountants. Public Accounting Firms must improve their auditors experience by enhancing variety of audit works and widening knowledge in various industries. Auditors must maintain their professional skepticism to provide appropriate assessment of audit evidence.